Mapeamento da integralidade do cuidado durante o pré-natal na atenção primária: scoping review - Barbieri, Melina Renata Blascke (Universidade Federal de São Carlos, 2020)
Healthcare centered on the pregnant woman and on collective prenatal care has been growing internationally and aims at valuing the needs of pregnant women, information sharing and social support for the construction of support networks, in addition to the clinical evaluation and other procedures of a traditional prenatal care. In the Brazilian scenario, there has been an increase in the coverage of prenatal care, as well as in the availability for procedure and routine protocols. However, the quality and effectiveness of the developed actions are less than expected. Thus, our study has as Objective: mapping the state of the art of prenatal care in primary care, according to the integrality of care; identifying the factors that are articulated with comprehensive prenatal care and assess the challenges and scope of comprehensive prenatal care in Brazil. Methods: It is a literature review, following the scoping review method, structured according to the protocol of the Joanna Briggs Institute. For the selection of the studies, we consulted digital libraries and multidisciplinary and health databases such as BDTD, CINAHL, COCHRANE, LILACS PUBMED, SCIELO, SCOPUS and WEB OF SCIENCE, selecting individual and international published material, available online from the beginning of 1980 until June 2019. 1,848 records were identified in the search, from which a sample of 26 studies was selected, among theses, dissertations and scientific articles, described in the recommendation of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (Prisma) flow diagram. Tables were made aiming at showing the selected studies, following numerical order, Study title, Place/Country/Year of publication, Type of Study, Theoretical-methodological approach, Population, Main results, Care Comprehensiveness Definition and Scope or Challenge, as well as the profile of the journals according to their year of publication, databases, continent, publication, country, study type, type of journal, approach, and study population. The thematic analysis followed four axes: Axis of Needs, Axis of Purposes, Axis of Articulation and Axis of Interactions, taking as parameters the axes of integrality idealized by Ayres, seeking a critical discussion on the scope and challenges of comprehensive prenatal treatment. Results: The most contemplated category in the achievement of comprehensive care was the one on the needs, which is, at the same time, the one that shows most challenges. The axis on articulation and the other ones showed the difficulties in reaching interdisciplinary knowledge and practices, pointing to the need for training and changes in professional posture, articulation of healthcare networks, cooperation between health and social sectors, participation and social mobilization. Final Considerations: The analyses we carried out allow us to conclude that, to achieve comprehensive care, it is necessary to value the quality of the intersubjective interactions in the care for pregnant women and in the construction of interdisciplinary teamwork. Care centered on the needs of pregnant women and their family has been shown to be an exemplary model of care and could be a guide for the reorganization of the work process.
Mapping comprehensive care during prenatal care in primary care: scoping review
Keywords: Cuidado pré-natal; Assistência integral à saúde; Garantia da qualidade dos cuidados de saúde; Pessoal de saúde; Gestantes; Prenatal care; Comprehensive health care; Health care quality guaranty; Health workers; Pregnant women; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM OBSTETRICA